Establishment of Neutralizing Rat Monoclonal Antibodies for Fibroblast Growth Factor-2 - Tanaka, Masako (Mary Ann Liebert, Inc., 2014)
Fibroblast growth factor-2 (FGF-2) plays a critical role in endothelial survival, proliferation, and angiogenesis and is localized on the cell membrane by binding to heparan sulfate proteoglycans. Here we established a neutralizing monoclonal antibody, 1B9B9, against FGF-2 using the rat medial iliac lymph node method. 1B9B9 blocked the binding of FGF-2 to its receptor, inhibiting FGF-2-induced proliferation and corresponding downstream signaling in endothelial cells. Treatment of human umbilical vein endothelial cells with 1B9B9 reduced the basal phosphorylation levels of Akt and MAPK. Furthermore, continued treatment with 1B9B9 induced cell death by apoptosis. Compared with FGF-2 knockdown, 1B9B9 significantly reduced cell survival. In addition, the combination of FGF-2 siRNA and 1B9B9 showed a synergistic effect. The data indicate that 1B9B9 established by the rat iliac lymph node method is a fully compatible neutralizing antibody.